A Note on the Mango Gall Midge (Procontarinia matteiana Kieffer & Cecconi) (Diptera: Cecidomycidae): A New Threat to Mango Industry in South Kordofan State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted to survey the incidence of mango gall midge(Procontarinia matteiana Kieffer & Cecconi) in South Kordofan State, Sudan. Twenty -two sites were visited. All inspected mango trees were infested. Field observations on thelife cycle of P. matteiana showed that egg and larval periods lasted 7-10 days, while thepupal stage took 5-7 days. The survey concluded that P. matteiana is widely distributedin South Kordofan State. Further studies on the life cycle, distribution and economicimportance of the mango gall midge is needed.